Nodulation of Retama monosperma by Ensifer aridi in an Abandonned Lead Mine Soils in Eastern Morocco - Lamin, Hanane; Alami, Soufiane; Bouhnik, Omar; ElFaik, Salma; Abdelmoumen, Hanaa; Bedmar, Eulogio J.; Missbah-El Idrissi, Mustapha (Frontiers in Microbiology, 2019)
Millions of tons of lead and zinc wastes from the abandoned Toussite mine are stored in the open air as dikes in the vicinity of the villages in Eastern Morocco and pose a real danger to both the environment and local populations. To prevent the movement of minerals to the nearby villages and limit the damages to the environment and health, we proposed the nitrogen-fixing leguminous shrub Retama monosperma, as a model plant to use for phytostabilization experimentations. This plant species is known by its ability to grow in hard climatic conditions and in heavy metals contaminated soils. The isolation of bacterial strains nodulating R. monosperma in the abandoned mine soils will permit the selection of rhizobia to inoculate young plant seedlings before their use for the phytostabilization of the mine tailings. In this work, forty-four bacteria were isolated from the root nodules of R. Monosperma grown in the Touissit abandoned mine. Twenty-four isolates were considered as true rhizobia as they possess a copy of the nodC symbiotic gene and were able to renodulate their original host. The phenotypic characterization showed that all the strains are tolerant in vitro to different concentrations of heavy metals. The analysis of the 16S rRNA sequences of two selected representative strains showed they were related to different strains of Ensifer aridi isolated from different legumes in three continents deserts. The glnII, recA and gyrB housekeeping genes analysis confirmed the affiliation of the strains to E. aridi. Moreover, the phylogenic analysis of nodA, nodC and nifH symbiotic genes showed that the strains are more related to Ensifer aridi JNVUTP6 species isolated from Tephrosia purpurea root nodules in the Thar Desert in India. To our knowledge, this is the first report about the isolation of E. aridi from R. monosperma root nodules.